Formation of ZnO nanoparticles in the presence of Tannic acid - Aqilah, Kamaruzaman; Nurul Akmal, Che Lah (Elsevier Ltd, 2020)
Zinc Oxide nanoparticles (ZnO NPs) have received abundance attention due to their ability to provide as a good semiconductor and UV absorbance materials. In this research, ZnO NPs are synthesised by hydrothermal method which employed a green synthesis method of which fully assisted by the Tannic Acid (TA). The controllable morphologies and mean sizes of ZnO NPs are observed to increased due to aggregation that occurred due to the influence of acidic medium (TA molecule). The morphological properties are discussed based on the TEM and FESEM images which indicated the average size of 14 nm and 32.7 nm for ZnO NPs and ZnO-TA NPs obtained, respectively. Meanwhile, the optical properties are discussed based on the UV-Vis absorbance spectroscopy results. The UV absorbance performance showed the behavior of absorbance peak at shorter wavelength as the ZnO NPs are capped with TA. The absorbance peak is shifted from UV-A region to UV-C region which indicated the transition from ZnO NPs to ZnO-TA respectively.